Proverbs and Idioms in Modern Shakespearean Adaptations: Multicultural Aspects - Sultan, Mr. Ahmed Essam; al-Asadi, Dr. Salam Hasan Makki Mutleb (Manar Elsharq Journal for Literature and Language Studies, 2024)
This is an essay that discusses traditional to modern allusions to multicultural Shakespeare. Major emphasis is placed on discussing proverbs and idiomatic expressions that help us understand the meanings of Shakespeare's plays, though they can be deeply hidden and difficult to catch for people from a completely different cultural context. Shakespeare transcends time and space to reach a place as diverse and sometimes as distant as the Indian subcontinent, where multiple versions and adaptations in and out of 12–13 languages are in vogue. Today, Shakespeare has transcended time and geography and is the subject of universal appeal. Appropriation opens doors to a novel method of interpretation; it allows us to revisit Shakespeare through the lens of another culture, which helps us place his universal themes within their specialized and narrow cultural and societal spheres. Idioms and proverbs, these customs, on the one hand, raise the play's setting and particularly display the customs of the characters working with the crowd. It has taken a moderate amount of work from these idiomatic expressions and proverbs in newer, creatively crafted versions of Shakespeare, and in this study, we have examined the role of these practices in adaptations of contemporary Shakespeare across geographic and encyclopedic borders.